Reducción de riesgo de desastres - Santana Trabucco, Eduardo Renato (2023)
In Peru, meteorological and hydrological phenomena can generate floods, increased flows, and the activation of streams that occur regularly. These scenarios cause human and material losses, as happened with the Yaku Cyclone, an uncommon phenomenon that occurred in March of this year. In this context, housing construction in inactive streams is a central problem. For this reason, we have created a communication strategy to contribute to the reduction of new buildings of this type through the education of adolescent schoolchildren residing in Chaclacayo, a district in the eastern area of Lima, located on inactive streams and their surroundings. The #ASaferFuture campaign, which we propose hypothetically from the NGO Save The Children, will provide information on Disaster Risk Reduction in the first phase and will organize a script and video contest on the digital platform TikTok, which adolescents must prepare to deepen their relationship with the message. Both activities will be led by their teachers, with whom the international organization will work directly.